MONITORING DAN EVALUASI PROGRAM DANA DESA (DD) SESUAI DENGAN UU NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Di Desa Landungsari Kecamatan Dau Kabupaten Malang Jawa Timur) - Dewi Citra Larasati; Muhammad Okto Adhitama (Universitas Tribhuwana Tunggadewi, 2017)
Abstract: This study analyzes the monitoring and evaluation mechanisms conducted by the local government against the Village Fund (DD) program. This study uses a qualitative method. Taking data using interviews that hold on the interview guide favorable (positive). Determination of informants using purposive sampling. Data analysis is done by multilevel method, with validity test of data triangulation and peer debriefing. The results showed that monitoring and evaluation were carried out with supervision from planning, implementation, report after program implemented and annual report, both physical and non physical program. Supervision is done by Local Government through BPD. Monitoring and evaluation mechanisms are seen from the availability and appearance of DD files, clarity of DD files, regulations used in DD management, accountability reports and see the impacts. So based on that, accountability of DD management has been considered good. It is also based on four principles of DD management that have been fulfilled, especially in relation to openness to the general public both in the preparation of the plan, implementation and in accountability. Keywords: Monitoring and Evaluation, Village Fund, Law No. 6 years 2014.